Pengaruh Pertumbuhan Perusahaan, Likuiditas, Ukuran Perusahaan, Dan Profitabilitas Terhadap Opini Audit Going Concern - Novita Wulandari; Ikhlasul Khair (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2026)
Purpose – This study aims to determine the effect of and Company Growth, Liquidity, Firm Size, and Profitability on Opini Audit Going Concern Design/methodology/approach – This research uses quantitative data, the sample in this study is the Property and Real Estate sector companies listed on the Indonesia Stock Exchange in the 2017-2022 in the period as many as 19 companies. The analysis technique used to test the hypothesis is multiple regression analysis using Eviews 9 software. Findings – The results of this study indicate that the Company Growth variable has a positive and statistically insignificant effect on the Opini Audit Going Concern, the Liquidity variable has a positive and statistically insignificant effect on the Opini Audit Going Concern, Firm Size has a negative and statistically significant effect on the Opini Audit Going Concern, Profitability has a positive and statistically insignificant effect on Opini Audit Going Concern. Research limitations/implications – This study discusses Opini Audit Going Concern and other factors such as Company Growth, Liquidity, Firm Size and Profitability which focus on Property and Real Estate sector companies